Determination of water requirement in a paddy field at Seberang Perak rice cultivation area - Mohamed Azwan, Mohamed Zawawi; Sa’ari, Mustapha, Assoc. Prof.; Zuzana, Puasa (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/